Possible genetic relationship between Mesozoic magmatic rocks and gold mineralization in the Jiaodong Peninsula (Eastern China): constraints of magmatic evolution and physicochemical conditions - Li, Jian; Dai, Chang-Guo; Wang, Chang-Wei; Song, Ming-Chun; Wang, Chang-Jiang; Li, Shi-Yong; Wang, Run-Sheng; Shi, Hong-Jiang; Xu, Kai-Lei; Wang, Ping (Frontiers in Earth Science, 2023)
The Jiaodong Peninsula is China's largest gold province and the third largest in the world. Although gold mineralization is associated with Mesozoic granites in temporal and spatial, the specific genetic association remains unclear, leading to ambiguity regarding the genetic type of gold deposits. To address this issue, we conducted whole-rock major and trace elements, LA-ICP-MS zircon U-Pb geochronology and trace elements geochemical analyses on the Linglong (Linglong suite), Yashan, and Nansu (Weideshan suite) plutons, and compiled contemporaneous magmatic rock data. Our results show that the granites were emplaced at 161 ± 2 Ma, 118 ± 1 Ma, and 121 ± 2 Ma, respectively. Geochemically, these rocks exhibit high Al2O3 (12.73-14.10 wt.%) content and Sr/Y (35.54-136.50) ratio, and low Y (3.26-11.20 ppm) and Yb (0.33-0.97 ppm) contents, indicating the adakitic rock properties. They were formed through partial melting of the thickened lower crust associated with subduction of the paleo-Pacific Plate. The Early Cretaceous granites contain a large amount of mafic microgranular enclaves, indicating the presence of mantle material mixing in the source area. Zircon trace elements show that the pre-mineralization magma (Linglong) had relatively low oxygen fugacity and temperature (ΔFMQ = -2.5 to +1.9, T-Ti in zircon (mean) = 740 °C) compared to the mineralization magma (ΔFMQ = +0.5 to +3.9, T-Ti in zircon (mean) = 755 °C). The physicochemical conditions in the pre-mineralization magma source area may be favorable for sulfide accumulation (may including gold). During the Early Cretaceous, North China Craton decratonization reached its climax, and a large number of adakitic crust-mantle mixed oxidized magma upwells, allowing for the migration and mineralization of a large amount of sulfides and gold. This model helps explain the transient, explosive, and genetic categories in Jiaodong gold deposits.